Sistem Pendukung Keputusan Menentukan Transfer Pemain Sepak Bola Menggunakan Metode AHP (Analytical Hierarchy Process) - Habib Putra Kusuma Negara; Edy Santoso; Heru Nurwasito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In recent years, football has turned out to be the one of the most favorite sport in world-wide and turn into a business of football transfer in continental Europe (Baihaqi, 2014). Football transfer is a critical process due to To increase the performance in the next season or replace player which is move to another club. However, by using manual method, it becomes time-consuming since a scout has to look the player weekly or yearly. Morever if the decision is bad, then a club may encounter losses which is from the transfer cost and player salaries. In order to solve this issues, decision support system for football transfer has been developed by employing Analytical Hirarcy Process (AHP). From the obtained result, the accuracy by using this system is 80% of six data testing. Therefore, AHP is an effective method in order to support the decision for football transfer.